An ethnographic qualitative study on the Malaysian preschool and special needs’ children home and school reading habits - Diyana, Kamarudin; Yasmin, Hussain; Applegate, Brooks; Mohd Hanafi, Mohd Yasin (Universitas Sebelas Maret, 2018)
This research is a qualitative research, exploring the reasons behind why the level of literacy in Malaysian students are quite low. The research delved into identifying ways to implement reading habits to preschool and special education children. The purpose which guides this research is that according to thestaronline.com on August 18th 2012, an online version of The Star newspaper from Malaysia, the average Malaysian only reads 2 books per year in 1996. This has made the Department of Higher Education worry about the level of proficiency in Malaysian students. This is a qualitative research utilizing open ended questionnaires and interviews as the main form of data collection. Parents were asked to document their open ended questionnaire and participate in an interview session in regards to their home reading habits with their children. In descending order, the themes found most important were implemented into school curriculum, parents should play a bigger role in children’s reading habits and early exposure. Results also indicated that parents in Malaysia do face problems when trying to implement reading culture into their daily lives.